2018
DOI: 10.14419/ijet.v7i4.38.24333
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Satisfaction with Interactive Forms of Training with Elements of Gamification

Abstract: The article considers students' satisfaction with interactive forms of training with elements of gamification. Based on the empirical study, the level of students’ satisfaction with interactive forms of training with elements of gamification has been measured. The study has been conducted at 6 educational organizations that carry out educational activities on educational programs of higher education – bachelor, specialist and master degree programs. A set of sociological methods has been used in the study: a q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
0
20
1
1
Order By: Relevance
“…The actions of linear management, HR specialists of companies, as well as specialized organizations involved in assessing the degree of development of natural intelligence in the system of talent management, constituted the external factor. In addition, they were engaged in staff training, introducing the game techniques for the development of the creative potential of talented employees into the practice in business structures [11] and during training at higher education institutions [12]; [13].…”
Section: A Experience Of Using Natural Intelligence In the Talent Mamentioning
confidence: 99%
“…The actions of linear management, HR specialists of companies, as well as specialized organizations involved in assessing the degree of development of natural intelligence in the system of talent management, constituted the external factor. In addition, they were engaged in staff training, introducing the game techniques for the development of the creative potential of talented employees into the practice in business structures [11] and during training at higher education institutions [12]; [13].…”
Section: A Experience Of Using Natural Intelligence In the Talent Mamentioning
confidence: 99%
“…The latter synthetic targets imply that a donor should have a non‐participating substituent at C‐2. With the help of this type of donor, 1,2‐ cis ‐glycosides may be conventionally obtained by the Lemieux reaction, by means of stereoselectivity control, by solvent effects, or by soft and slow promotion of 1,2‐ trans ‐imidates and thioglycosides . But none of them provides universal and reliable preparation of 1,2‐ cis ‐glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the analysis of the scientific literature and the results of the sociological research conducted, it has been established that the students are more satisfied with the quality of interactive sessions with elements of gamification (57.01 %) than with the quality of training by traditional methods (23.36 %) and the quality of the content of classes conducted by traditional methods (19.63 %). It has been revealed that the use of interactive forms of training with elements of gamification is the most effective: to increase the effectiveness of mastering the training material (20 %) (Demchenko, Vinichenko, 2018).…”
Section: Discussionmentioning
confidence: 99%